A surface-grafted thermoresponsive hydrogel in which the surface structure dominates the bulk properties. Issue 74 (2nd August 2016) - Matsukawa, Ko; Masuda, Tsukuru; Akimoto, Aya Mizutani; Yoshida, Ryo
Abstract : A surface-grafted hydrogel was successfully synthesized by immobilization of the ATRP initiator at the surface region of the gel and the subsequent ARGET ATRP step. Abstract : A surface-grafted hydrogel was successfully synthesized by immobilization of the ATRP initiator at the surface region of the gel and the subsequent ARGET ATRP step. This is the first example of a bulk hydrogel with a dense surface-localized layer of a grafted polymer and "active" permeation control of the gel.